2019
DOI: 10.3390/ma12091477
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Transformation Zone Activation during Loading and Unloading in Nanoindentation of Metallic Glasses

Abstract: Using molecular dynamics simulation, we study nanoindentation in large samples of Cu–Zr glass at various temperatures between zero and the glass transition temperature. We find that besides the elastic modulus, the yielding point also strongly (by around 50%) decreases with increasing temperature; this behavior is in qualitative agreement with predictions of the cooperative shear model. Shear-transformation zones (STZs) show up in increasing sizes at low temperatures, leading to shear-band activity. Cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
(94 reference statements)
2
15
0
Order By: Relevance
“…Also, the active zone increases with temperature, suggesting more localized plastic events for low temperatures. This effect is well known and has been reported in nanoindentation studies [8,31,45] and other loading experiments [46][47][48]. From the top view snapshots, a very noticeable activity can be observed at the surface of the sample with increasing temperature, with no shear-band formation at the surface at any of the studied temperatures.…”
Section: Active Zonessupporting
confidence: 76%
See 1 more Smart Citation
“…Also, the active zone increases with temperature, suggesting more localized plastic events for low temperatures. This effect is well known and has been reported in nanoindentation studies [8,31,45] and other loading experiments [46][47][48]. From the top view snapshots, a very noticeable activity can be observed at the surface of the sample with increasing temperature, with no shear-band formation at the surface at any of the studied temperatures.…”
Section: Active Zonessupporting
confidence: 76%
“…A crystalline mixture was first heated to a temperature above the melting point, T = 2000 K, for a time period of 500 ps and then cooled to the final temperature with a quenching rate of 0.01 K/ps to obtain the metallic glass. We note that we studied previously the effect of the quenching rate on the plastic properties of the glass and found that the quenching rate adopted here is sufficiently slow to obtain reliable results on the glass plasticity [31]. The glass transition temperature T g for this particular composition and potential is around 1000 K for a quenching rate of 1 K/ps [32]; for the quenching rate adopted here there would be a slight change of T g toward a lower temperature, but not below 800 K. Here, we simulated samples at 5 different temperatures.…”
Section: Methodsmentioning
confidence: 88%
“…Additionally, we correlate the core densities with the indentation hardness values determined for the same samples in Ref. 18. These results are shown in the inset of Fig.…”
mentioning
confidence: 72%
“…Plastic-zone size factor f as a function of temperature. Inset: Hardness[18] as a function of the core plastic density, ρ max .…”
mentioning
confidence: 99%
“…The resulting avalanche of sessile STZ activations may lead to localised flow in the form of shear bands, which may ultimately lead to material failure. Extensive numerical [130][131][132][133][134][135] and some indirect experimental [136][137][138] evidence exists for the inelastic deformation of metallic and polymeric glasses at T/T g < 1 (and at moderate strain rates) to be governed by STZ dynamics.…”
Section: Mesoscale Modelling Via Shear Transformation Zone (Stz) Dynamentioning
confidence: 99%